94 Key information summary (KIS) generation for people who died in scotland in 2017: a mixed methods study. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Finucane, Anne; Davydaitis, Deborah; Horseman, Zoe; Carduff, Emma; Tapsfield, Julia; Baughan, Paul; Meade, Richard; Warren, Tim; Spiller, Juliet; Thompson, Ian; Boyd, Kirsty; A Murray, Scott
Abstract : Introduction: Key Information Summaries (KIS), introduced throughout Scotland in 2013, are shared electronic clinical summaries used to guide urgent care in the community and emergency hospital admission. The percentage of people with a KIS at the time of death can act as an indicator of access to palliative care. Aims: To estimate the extent of KIS generation for people who die with an advanced progressive condition. To explore GP perspectives of commencing and updating a KIS. Methods: A retrospective review of the electronic records of all patients who died in 18 Scottish general practices in 2017; semi-structured interviews with one healthcare professional in each practice. Results: Data on 1304 decedents was collected (49% female, 51% male). Of these, 1034 had an advanced progressive condition at the time of death. 69% died with a KIS. This was highest for patients with cancer (80%). Of the 712 patients with a KIS, 69% (n=488) had resuscitation status recorded. 60% had a next of kin name documented in the KIS. 52% of KISs were highly useful (clear plan regarding patient wishes concerning current care and future planning), 45% were useful. 37% of patients with a KIS died in hospital, compared with 65% without a KIS. The special notes section was considered the most useful part of the KIS. Conclusion: The proportion of patients with an advanced progressive condition who have a KIS at the time of death has increased from 60% in 2014 (Tapsfield et al 2016) to 69% in 2017. KISs are nearly always perceived as useful or highly useful, and are associated with a higher likelihood of dying in a community setting. Better information regarding next of kin/carers would further improve KIS quality, and a renewed focus on KIS generation for people with organ failure is warranted.